A community pharmacy-led intervention for opioid medication misuse: A small-scale randomized clinical trial. (1st December 2019) - Cochran, Gerald; Chen, Qi; Field, Craig; Seybert, Amy L.; Hruschak, Valerie; Jaber, Amanda; Gordon, Adam J.; Tarter, Ralph
Highlights: Community pharmacy may be a scalable setting to address opioid medication misuse. The intervention in this study may be acceptable/feasible for patient delivery. The intervention in this study may improve opioid misuse, pain, and depression. Abstract: Background: Stemming the opioid epidemic requires testing novel interventions. Toward this goal, feasibility and acceptability of a Brief Motivational Intervention-Medication Therapy Management (BMI-MTM) intervention was examined along with its impact on medication misuse and concomitant health conditions. Methods: We conducted a two-group randomized trial in 2 community pharmacies. We screened patients for prescription opioid misuse at point-of-service using the Prescription Opioid Misuse Index. Participants were assigned to standard medication counseling (SMC) or SMC + BMI-MTM (referred to as BMI-MTM herein). BMI-MTM consists of a pharmacist-led medication counseling/brief motivational session and 8-weekly patient navigation sessions. Assessments were at baseline, 2-, and 3-months. Primary outcomes included feasibility, acceptability, and mitigation of opioid medication misuse. Secondary outcomes included pain and depression. Outcomes were analyzed with descriptive and multivariable statistics (intent-to-treat [ITT] and adjusted for number of sessions completed [NUMSESS]). Results: Thirty-two participants provided informed consent (74.4% consent rate; SMC n = 17, BMI-MTM n = 15; 3-month assessment retention ≥93%). Feasibility was demonstrated by all BMI-MTM recipients completing the pharmacist session and an average of 7 navigation sessions. BMI-MTM recipients indicated ≥4.2 (5 maximum) level of satisfaction with the pharmacist-led session, and 92.4% were satisfied with navigation sessions. Compared to SMC at 3-months, BMI-MTM recipients reported greater improvements in misuse (ITT: Adjusted Odds Ratio [AOR] = 0.13; 95% CI = 0.05, 0.35, p < 0.001. NUMSESS: AOR = 0.05; 95% CI = 0.01, 0.25; p < 0.001), pain (ITT: В = 8.8, 95% CI=-0.95, 18.5, p = 0.08; NUMSESS: В = 14.0, 95% CI = 3.28, 24.8, p = 0.01), and depression (ITT: B= -0.44; 95% CI=-0.65, -0.22; p < 0.001. NUMSESS: B= -0.64; 95% CI=-0.82, -0.46; p < 0.001). Conclusions: BMI-MTM is a feasible misuse intervention associated with superior satisfaction and outcomes than SMC. Future research should test BMI-MTM in a large-scale, fully-powered trial.